Throughput enhancement for WLAN TV white space in coexistence of IEEE 802.22 - Saeed R.A.; Ismail A.F.; Hasan M.K.; Mokhtar R.; Salih S.K.A.; Hashim W. (Indian Society for Education and Environment, 2023)
This paper proposes an algorithm for coexistence in TVWS between IEEE 802.22 and IEEE 802.11af by equal opportunity without increased delay time and decreased throughput, for each of them. Also, an investigation has been conducted for the coexistence problem between the 802.22 and the IEEE 802.11af systems, in the TV White Spaces (TVWS). IEEE 802.22 and IEEE 802.11af are two typical standards envisioned to be widely adopted in the future. However, these two standards are heterogeneous in both power level and PHY/MAC design; as a result coexistence challenge is there. The main focus of this paper is to design a co-channel coexistence scheme for the IEEE 802.22 customer-premises equipment's (CPEs) as well as the IEEE 802.11af systems. In this paper, the challenges are identified to enable the co-channel coexistence of the IEEE 802.22 and the IEEE 802.11af systems. Afterwards, an algorithm is proposed for coexistence, depending on frame times. The algorithm is applied in two networks in three cases, depending on the amount of transmitting data. The simulation results suggest that the proposed solution has increased the throughput and decreased the waiting time by a noticeable way for IEEE 802.11af.